Integrated Health Education (IHE) Method: An Impact on Tuberculosis Health Education for the Sub-district of Sumowono Society, Indonesia - Rahayu, Sri Ratna; Fauzi, Lukman; Semadi, Ngakan Putu Djaja; Rizqi, Nisrina Dwi; Prehamukti, Anggit Aprindrian; Lestari, Susanti; Firdhausy, Hima Sakina; Merzistya, Aufiena Nur Ayu; Khasanah, Amelia Fitra (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
Tuberculosis (TB) case results in Semarang Regency is still in the low category. The IHE method was developed through counseling and training to support the community empowerment needed in assisting TB cases handling and determination. This study aims to determine the IHE method's effect and effectiveness on the knowledge and attitudes of Pemberdayaan Kesejahteraan Keluarga (Empowerment of Family Welfare; PPK) members regarding TB disease. A quasi-experimental one-group pretest-postest design and a sample size of 25 active PKK members in the Sumowono sub-district were used. Then, the data were analyzed using the Wilcoxon test and N-Gran Score. The results showed the IHE method's effect on PKK members knowledge and attitudes regarding TB disease with P-values of 0.034 and 0.029, respectively. The IHE method effectively improved the PKK members attitudes towards TB disease (mean= 61.43%). There was an increase in the knowledge and attitudes of PKK mothers about TB disease through health education using the IHE method. The development in IHE is needed to be applied as a health education method in various other diseases.